Unveiling Echoes: Memory Activism in Kazuo Ishiguro’s When We Were Orphans - Preethika. B; Dr Shantichitra K (Educational Administration: Theory and Practice, 2024)
This study is to examine the idea of Atlterego events experienced by character Christopher Bank, from when we were orphans. This novel deals with the combination of memory and activism. The characters in the novel undergo the strange holocaust due to war in Shanghai. Bank faced a lonely childhood after his attainment of adulthood, he is deliberately pushed to shift in an alterego that is been very visibly exposed. This paper concentrates on two typical contrasting points in regards with memory. One, is explained by the combination of substantive memory with that of alterego. Second, activism is being analysed in antithetical conditions. The main purpose of this memory studies is to reconfiguration ambivalent thoughts that protagonist's and Ishiguro's reminisce with their individual understanding.